The Réunion Fody and Sonnerat’s Shrew and the validity of scientifically naming animals described without physical types - Cheke, Anthony S.; Hume, Julian P. (Zootaxa, 2018)
An essential requirement of the current edition of the International Code of Zoological Nomenclature (ICZN 1999) is to designate a holotype or syntypes for a species or subspecies newly described after 1999. Where specimens exist this makes sense (and is indeed essential), but is meaningless when describing a species-group taxon from an old illustration or written account in which specimens were not preserved or even necessarily taken at all. The naming of two species which one or both of us described post-1999 from old accounts without designating types has been singled out as invalid on this basis. As the revisers of the ICZN apparently did not anticipate further naming of taxa from old accounts, and thus allowed a logical paradox to arise, we strongly recommend that, in respect of descriptions from old accounts with no specimens, this rule be waived by a retrospective amendment, as it is likely that other similar cases exist, and it serves no-ones’ interest to strike down otherwise properly described names on a pointless technicality. Prior to our proposed change in the Code, in this note Foudia delloni Cheke & Hume sp. nov. (Aves: Passeriformes: Ploceidae), from Réunion Island, and Diplomesodon sonnerati Cheke sp. nov. (Mammalia: Soricomorpha: Soricidae), from southern India, are named anew using the same names and the original diagnoses.